Choroidal Changes in Patients with Diabetic Retinopathy: A Retrospective Study - Shu-Yu Peng; Ta-Ching Chen; Yi-Ting Hsieh; Tzyy-Chang Ho; Chung-May Yang; Chang-Hao Yang (Diagnostics, 2024)
This study aimed to investigate the characteristic choroidal changes in patients with diabetic retinopathy and identify factors affecting choroidal thickness (CTh), choroidal vascular index (CVI), and choriocapillaris flow. We retrospectively analyzed 79 eyes of 48 patients with diabetes between August 2021 and February 2022. We collected laboratory data, including HbA1c, serum creatinine, blood urea nitrogen, triglyceride, total cholesterol, high-density lipoprotein, and low-density lipoprotein (LDL) levels. Optical coherence tomography images of the foveal avascular zone, retinal vascular density, choroidal flow, retinal thickness, CTh, and CVI were analyzed. Possible determining factors affecting CTh, CVI, and choriocapillaris flow were analyzed using nonparametric multivariate analysis. LDL (p < 0.001) positively correlated with CTh, whereas CVI (p = 0.007) was negatively correlated with CTh in diabetic patients with diabetes. We also identified a negative correlation between choriocapillaris flow and deep parafoveal retinal vessel density in patients with low-grade diabetic retinopathy (DR), which diminished in those with more advanced DR. Our study provides further information on the changes in choroidal structure and blood flow in patients with diabetes.